[Un]succesful "metabolization" of the Northern Irish War: The post-troubles trauma in Glenn Patterson's writing - Bartnik, Ryszard (Adam Mickiewicz University, 2009)
Northern Irish literature of the last decade illustrates an arduous effort of the Ulster men to break down the walls of political and cultural partition. Yet, even though the Northern Irish community tends to present itself in terms of a variety of images, the ultimate impression is that the recent novelistic and critical productions resonate with past antagonisms and the post-Troubles trauma. It is so since the North, as many a scholar indicates, is as if fated to continually recompose its past. This paper then, set against the background of the civil war experiences, discusses Glenn Patterson’s excavation of individual and collective memories which prove that the dead are constantly materializing in today’s Northern Irish reality. Hence, Glenn Patterson’s accumulation of voices by means of which the author ponders over the politics of memory and imparts knowledge of the characters who, on a long journey out of the darkness into the space of light, find some vestiges of the old conflicts still echoing and rather difficult to hush up.